2020
DOI: 10.1101/2020.05.15.098301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-channel intraneural vagus nerve recordings with a novel high-density carbon fiber microelectrode array

Abstract: 25Autonomic nerves convey essential neural signals that regulate vital body functions. Recording 26 clearly distinctive physiological neural signals from autonomic nerves will help develop new 27 treatments for restoring regulatory functions. However, this is very challenging due to the small 28 nature of autonomic nerves and the low-amplitude signals from their small axons. We developed 29 a multi-channel, high-density, intraneural carbon fiber microelectrode array (CFMA) with ultra-30 small electrodes (8-9 µ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…However, we were unable to confirm if all spikes on a given channel were from a single or multiple axons due to similarity in spike waveform shapes and normal variations in amplitude. The observation of one unit typically sorted per electrode in a nerve fascicle is consistent with prior studies of microelectrode interfacing with peripheral nerves [8,38] . Intraneural recordings from peripheral nerves, such as shown here, may have significant utility in studying organ and limb neurophysiology and in providing sensory feedback for neuroprostheses.…”
Section: Acute Neural Recordings Responding To Cutaneous Brushing Stimulationsupporting
confidence: 87%
See 1 more Smart Citation
“…However, we were unable to confirm if all spikes on a given channel were from a single or multiple axons due to similarity in spike waveform shapes and normal variations in amplitude. The observation of one unit typically sorted per electrode in a nerve fascicle is consistent with prior studies of microelectrode interfacing with peripheral nerves [8,38] . Intraneural recordings from peripheral nerves, such as shown here, may have significant utility in studying organ and limb neurophysiology and in providing sensory feedback for neuroprostheses.…”
Section: Acute Neural Recordings Responding To Cutaneous Brushing Stimulationsupporting
confidence: 87%
“…The development of intrafascicular devices enabled researchers to detect and modulate neural activities at a higher resolution. To date, a variety of intrafascicular recording and/or stimulation methods have been achieved using thin-film polymer devices [6,7] , carbon fiber electrode arrays [8,9] , highly conductive carbon-based threads with low electrochemical impedance [10][11][12] , Utah arrays [13,14] , flexible microneedle electrode arrays [15][16][17] and regenerative devices [18] . With implantation of such devices, researchers were able to map and decode motor and/or sensory somatic or autonomic systems at a sub-fascicular level [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Six Flex Arrays with SCFs of 200-250 µm length, as represented in Figure 1C, were inserted into the left CVN of 22 Sprague-Dawley rats ( Figure 5E, Supplemental Video 3). Detailed characterization of the population recordings is presented in a companion study by Jiman et al 2020. In all experiments, we visually observed successful insertion of all SCFs into the vagus nerve after an average of 2.3 insertion attempts. The functional SCFs Figure 5.…”
Section: Acute Electrophysiology Recordings From Rat Cervical Vagus Nmentioning
confidence: 94%
“…We observed that 19.8% of functional SCFs recorded neural clusters with SNRs > 4. The maximum mean Vpp was found to be 91.72 µV (Jiman et al, 2020).…”
Section: Acute Electrophysiology Recordings From Rat Cervical Vagus Nmentioning
confidence: 94%
See 1 more Smart Citation